PEMBANGUNAN DAN PEMBERDAYAAN MANUSIA MELALUI DANA DESA: POLA DARI MASA LALU HINGGA SINERGITAS YANG RANCU - Cahyadi, Ashadi (Institut Agama Islam Negeri Bengkulu, 2019)
Nawa Cita requires the village as the core of development. Funds are rolled outfor each village to support the development, empowerment, and welfare of somevillage subjects. The main assumption is that the synergy of infrastructurefollowed by community empowerment will produce sustainable welfare. Thisrationality is considered not running together because it provides a largeportion of the infrastructure and understates human empowerment. This studytried to discuss village funds by reviewing past development patterns,community development, and correcting infrastructure-based development. Thediscussion in this paper has been supported by various journals, figures, andnews from online media. All materials are read interactively, reduced, then theessence of reading is developed according to inductive reasoning. It was foundthat from the past, village programs always referred to the provisions of thecentral government. Even though the problems and needs of each village arevery different. Then, the lack of understanding of the village apparatus about theprogram, it is not uncommon for programs to be rolled out to be replicas fromother villages. This paper also discusses community-based development as asolution to village fund problems.